Identifying career development intervention by counsellors for manufacturing production workers - Adanan, Mona Adlina; Abdul Kadir, Rusnani (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
This conceptual paper discusses the career development interventions used in organisations for their employees. It also tries to identify the suitable career development intervention that can be considered by career counsellors as career development intervention programme for manufacturing production workers.